Synthesis and characterization of Zn 3Nb 2O 8 nanopowders via a rapid vibro-milling technique - Pakawanit P. (2014)
The simple mixed-oxide method via a rapid vibro-milling technique is explored in the preparation of pure zinc niobate (Zn 3Nb 2O 8) nanopowders. The formation of the phase in the calcined powders has been investigated as a function of calcination conditions by TG-DTA and XRD techniques. Morphology, particle size and chemical composition have been determined via a combination of SEM/TEM and EDX techniques. It has been found that the minor phase of ZnNb2O6 tends to form together with the Zn 3Nb 2O 8 phase, depending on calcination conditions. More importantly, it is seen that optimization of calcination conditions can lead to a single-phase Zn 3Nb 2O 8 in a monoclinic phase. © 2013 Copyright Taylor and Francis Group, LLC.